The Effect of Using Contextual Teaching and Learning to Eighth Graders' Reading Comprehension at SMP 3 PSKD Jakarta - Sianipar, Fransisca Lafayette (JET (Journal of English Teaching), 2018)
AbstractThis research was an experimental research. It aimed to investigate the effect of using Contextual Teaching and Learning method on students’ reading comprehension to the eighth graders at SMP 3 PSKD Jakarta. To meet the aim, this research was conducted in two classes. Each class consisted of 30 students. The experimental group (VIII A) was taught using CTL method and control group (VIII B) was taught using drilling method. The classes were held twice a week and the research was conducted over a period of one months. Pre-test and post-test were employed to collect data. Both the pre-test and the post-test were administered in the two groups. The data ere analyzed using SPSS version 19.0 software. These data analysis were applied for analyzing the data obtained from four sets of tests. Data analysis showed that there is a significant effect of using Contextual Teaching and Learning Method toward students’ reading comprehension. It can be seen through the mean scores of post-test in the experimental group is 16.10 and the mean score of post-test in the control group is 15.95. Based on the result it can be said that Contextual Teaching and Learning significantly affected the eighth graders’ reading comprehension at SMP 3 PSKD Jakarta. Keywords: experimental research, contextual teaching and learning, reading comprehension